ANALISIS PENGARUH GRATIS ONGKIR DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI LAYANAN MAKANAN ONLINE PADA GEN Z DI SURABAYA - Muhammad Roshin Anwar; Jannatul Ma’wa Ma’wa; Aisyah Maretha Putri; Adelia Virnanda P.S; Musdalifah Adilah (Archetype : Jurnal Ilmiah Psikologi dan Terapan, 2026)
The development of online food delivery applications has transformed the consumption patterns of Generation Z in Surabaya through digital promotional strategies such as free shipping and discounts. Purchasing decisions are influenced not only by functional needs but also by the economic incentives offered by digital platforms. This study aims to analyze the effect of free shipping and discounts on the purchasing decisions of Generation Z in online food delivery applications in Surabaya. A quantitative approach was employed, with data collected through online questionnaires distributed to 78 Generation Z respondents using a four-point Likert scale. Data analysis was conducted using multiple linear regression with a 5% significance level. The results indicate that free shipping and discounts, both simultaneously and partially, have a positive and significant effect on purchasing decisions, with discounts being the most dominant variable. These findings confirm that price-based promotional strategies remain a key factor in driving Generation Z’s purchasing decisions on online food delivery platforms.